Performance simulation of grid-connected rooftop solar PV system for small households: A case study of Ujjain, India - Chandrakant Dondariya; Deepak Porwal; Anshul Awasthi; Akash Kumar Shukla; K. Sudhakar; Murali Manohar S. R.; Amit Bhimte (Energy Reports, 2018)
Solar rooftop PV system is an attractive alternate electricity source for households. The potential of solar PV at a given site can be evaluated through software simulation tools. This study is done to assess the feasibility of grid-connected rooftop solar photovoltaic system for a household building in holy city Ujjain, India. The study focuses on the use of various simulation software, PV*SOL, PVGIS, SolarGIS and SISIFO to analyze the performance of a grid-connected rooftop solar photovoltaic system. The study assesses the energy generation, performance ratio and solar fraction for performance prediction of this solar power plant. PV*SOL demonstrates to be easy, fast, and reliable software tool for the simulation of a solar PV system.
Keywords: 330; Photovoltaic; Energy; Solar; Grid; PV*SOL; PVGIS; SISIFO; SOLARGIS